2006
DOI: 10.1073/pnas.0602818103
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for targeting HIV-1 Gag proteins to the plasma membrane for virus assembly

Abstract: During the late phase of HIV type 1 (HIV-1) replication, newly synthesized retroviral Gag proteins are targeted to the plasma membrane of most hematopoietic cell types, where they colocalize at lipid rafts and assemble into immature virions. Membrane binding is mediated by the matrix (MA) domain of Gag, a 132-residue polypeptide containing an N-terminal myristyl group that can adopt sequestered and exposed conformations. Although exposure is known to promote membrane binding, the mechanism by which Gag is targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
774
8
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 518 publications
(840 citation statements)
references
References 66 publications
46
774
8
4
Order By: Relevance
“…As an alternative, we generated membrane-bound GM-CSF by tethering it with GPI anchors from CD59 or LFA3. Interestingly, the GPIanchored GM-CSF was found to be incorporated at higher levels into the VLPs than GM-CSF TM-gp160 , presumably because GPI-anchored proteins associate with lipid rafts, which are used as sites for HIV assembly (34,41). In addition, the enhanced activity of SIV VLPs with GPI-anchored GM-CSF in vivo could possibly be attributed to greater flexibility and less steric constraints of the GPI anchor.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, we generated membrane-bound GM-CSF by tethering it with GPI anchors from CD59 or LFA3. Interestingly, the GPIanchored GM-CSF was found to be incorporated at higher levels into the VLPs than GM-CSF TM-gp160 , presumably because GPI-anchored proteins associate with lipid rafts, which are used as sites for HIV assembly (34,41). In addition, the enhanced activity of SIV VLPs with GPI-anchored GM-CSF in vivo could possibly be attributed to greater flexibility and less steric constraints of the GPI anchor.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical shift changes of "group 2" were observed for WT myrMA upon addition of di-C 4 -PI(4,5)P 2 and NMR-based structural studies confirmed that they reflect di-C 4 -PI(4,5)P 2 -dependent exposure of the myristyl group. 31 In addition, intermolecular NOEs between protein residues and myristate group are clearly observed in the 3D 13 C-edited/ 12 C-double-half-filtered NOE experiment obtained for the V7R:di-C 4 -PI(4,5)P 2 complex (Figure 7), indicating that di-C 4 -PI(4,5)P 2 binding does not trigger myristyl exposure.…”
Section: Pi(45)p 2 Binds To Myrma Mutants But Does Not Trigger Myrismentioning
confidence: 95%
“…In addition, the relative NOE intensities and cross-peak patterns matched the data obtained for the WT myr(s)MA protein. 27,31 The main differences between the structures are localized within the disordered loop formed by residues Gly-2 -Ser-9. For V7R, the side chain of Arg-7 is poised to make a salt bridge with the side chain of Glu-52, and the mythelene groups of Arg-7 contribute to the hydrophobic interactions with the methylene groups of the myristate ( Figure 6).…”
Section: Structures Of V7r-and L8a-myrmamentioning
confidence: 99%
“…However, one simple hypothesis to explain the poor neutralization by anti-PIP in the pseudovirus/ TZM-bl system compared to that in the PBMC assay is that the anti-PIP antibodies might neutralize HIV-1 by binding to viral lipids when the lipid bilayer of the virus directly interacts with the lipid bilayer of the target cell. A further possibility is that anti-PIP reacts with phosphatidylinositol-4,5-bisphosphate during viral assembly and budding (27). In either case, such binding of anti-PIP to the viral lipids might be sterically hindered by excessively high levels of adjacent CCR5 protein on the TZM-bl target cell when the viral and plasma membrane lipid bilayers are closely apposed.…”
mentioning
confidence: 99%